(untitled) (MAUSAM, 1988)
A multiple linear regression equation has been derived for estimating sugarcane yield at Padegaon in Maharashtra, using some of the weather parameters at specific periods of crop growth. The data employed for deriving the actual regression equation is from 1950 to 1969. The regression equation accounts for 76 per cent variation in the estimated yield. The departure of predicted sugarcane yields from actual yields for 1970 and 1971 are observed to be 8 per cent and 11 per cent respectively.